(untitled) (American Journal of Islam and Society, 1998)
The term globe in the English language enjoys the same meaning as the English word world. The term globalization is now used to denote a trend in world affairs in which several factors and forces impact on the way we view ourselves, our world, societies, cultures, the physical world, and the rest of the universe. The Arabic word for this geographic world is ‘ciZum; hence, the Qur’anic usage describing the Creator as Rabb uZ ‘&zmSn (The Lord of the Worlds). This Islamic term conjures up an image that cuts across the vast range of beings and their domains of existence in creation. The understanding of globalization that is beginning to gain acceptance throughout the world centers on the hegemony of the mass media in the realm of human consciousness. To put the matter humorously, one can say that the electron has now become the secret mediator between people located in one part of the world and their counterparts located elsewhere on the globe. It was this image that led the late Marshall MacLuhan to use the metaphor of the tele-village to describe what he believed was happening in the area of human communications. Globalization now manifests itself in five important ways. The first involves the shortening of geographic distances and the ease of human travel via faster means of locomotion, such as supersonic planes, nuclear- powered ships, high-speed cars, and bullet trains. These modem means of travel have combined to create a new world order for humanity. The world is no longer a wild place where humans must battle with other zoological rivals; rather, it has become a place where human creativity and power now reign supreme, if matters are seen through the eyes of nonhuman flora and fauna. The second manner in which globalization is shaping our world is in the traversing of physical distances through the effective manipulation of the electron in the service of humanity. By virtue of humanity’s scientific ...